2020
DOI: 10.4025/actasciagron.v42i1.44249
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes and development of soybean with use of pelletized organomineral fertilizer containing sewage sludge and filter cake

Abstract: Filter cake has been one of the most widely used waste products as a source of organic matter in the production of biofertilizers. However, sanitized sewage sludge is a recommended alternative for agricultural use because of environmental issues. Studies that examine the use of this particular class of fertilizer are needed. The objective of this work was to evaluate the efficiency of sewage sludge and filter cake as sources of organic matter in the composition of pelletized biofertilizers for soybean producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Their findings suggested that the SS amendment was helpful to accelerate germination most efficiently at a 2.5% rate. Similarly, Silva et al [41] also conducted laboratory pot experiments to Previously, Cristina et al [40] studied the impact of biogas digestate obtained from SS on the seed germination potential of garden grass (Lepidium sativum). Their findings suggested that the SS amendment was helpful to accelerate germination most efficiently at a 2.5% rate.…”
Section: Impact Of Pgpr and Ss On Ridge Gourd Seedling Germinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings suggested that the SS amendment was helpful to accelerate germination most efficiently at a 2.5% rate. Similarly, Silva et al [41] also conducted laboratory pot experiments to Previously, Cristina et al [40] studied the impact of biogas digestate obtained from SS on the seed germination potential of garden grass (Lepidium sativum). Their findings suggested that the SS amendment was helpful to accelerate germination most efficiently at a 2.5% rate.…”
Section: Impact Of Pgpr and Ss On Ridge Gourd Seedling Germinationmentioning
confidence: 99%
“…Their findings suggested that the SS amendment was helpful to accelerate germination most efficiently at a 2.5% rate. Similarly, Silva et al [41] also conducted laboratory pot experiments to study the biochemical effects of SS application on soybean (Glycine max). They reported that both SOD and CAT activities were positively correlated with the applied SS dose (0, 50, and 100%).…”
Section: Impact Of Pgpr and Ss On Ridge Gourd Seedling Germinationmentioning
confidence: 99%
“…These aim to reduce leaching losses of the mineral nutrients applied to soil by releasing the nutrients more slowly and gradually, thereby guaranteeing a more prolonged residual fertilizer effect [1,2]. Among these technologies, organomineral fertilizers (OFs) are an efficient way of supplying nutrients and organic matter when compared with exclusively mineral sources [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Also, organic wastes have been reported to influence the nutrient composition of the soil [15]. The influence of organic waste in soil includes increasing soil nutrients and reducing or immobilizing otherwise detrimental soil minerals such as aluminum (Al) [15][16][17]. The use of organic wastes for soil enhancement has also been reported to improve soil structure and the ability of soil to hold water for plant use [1,7,15].…”
Section: Introductionmentioning
confidence: 99%